Functional analysis of phospholipase Dδ family in tobacco pollen tubes - Pejchar, Přemysl; Sekereš, Juraj; Novotný, Ondřej; Žárský, Viktor; Potocký, Martin (The Plant journal, 2020)
Phosphatidic acid (PA), an important signalling and metabolic phospholipid, is predominantly localized in the subapical plasma membrane (PM) of growing pollen tubes. PA can be produced from structural phospholipids by phospholipase D (PLD), but the isoforms responsible for production of PM PA were not identified yet and their functional roles remain unknown. Following genome-wide bioinformatic analysis of the PLD family in tobacco, we focused on the pollen-overrepresented PLDδ class. Combining live-cell imaging, gene overexpression, lipid-binding and structural bioinformatics, we characterized five NtPLDδ isoforms. Distinct PLDδ isoforms preferentially localize to the cytoplasm or subapical PM. Using fluorescence recovery after photobleaching, domain deletion and swapping analyses we show that membrane-bound PLDδs are tightly bound to PM, primarily via the central catalytic domain. Overexpression analyses suggested isoform PLDδ3 as the most important member of the PLDδ subfamily active in pollen tubes. Moreover, only PLDδ3 shows significant constitutive PLD activity in vivo and, in turn, PA promotes binding of PLDδ3 to the PM. This forms a positive feedback loop leading to PA accumulation and the formation of massive PM invaginations. Tightly controlled production of PA generated by PLDδ3 at the PM is important for maintaining the balance between various membrane trafficking processes that are crucial for plant cell tip growth.
Keywords: membrane trafficking; Phospholipase D; pylová láčka; Plant Proteins; Nicotiana; tip growth; phospholipase D; fosfolipasa D; rostlinné proteiny; phosphatidic acid; Phylogeny; Pollen Tube; rostlinné geny; pollen tube; Pollen; pyl; tobacco; Isoenzymes; fylogeneze; tabák; Genes, Plant; izoenzymy; Nicotiana tabacum